(untitled) (XXI Century. Spanish Literature and Culture, 2024)
This paper offers, in its introduction, as a state of the art, a review of El poeta y la ciudad. Nueva York y los escritores hispanos (1994), by Dionisio Cañas, and, mostly, an exhaustive review of Historia poética de Nueva York en la España contemporánea (2012), by Julio Neira. Due to the absence in its pages of Antonio Gala, a detailed analysis is carried out both author’s prose, ranging from his articles to his autobiography, and of his poetry, focused on the texts of El poema de Tobías desangelado (2005). With all this, Gala’s vision of New York is precisely outlined.